UFMylation maintains YAP stability to promote vascular endothelial cell senescence - Yanan Liu; Min Zuo; Aiwei Wu; Zhaoxiang Wang; Siting Wang; Yongping Bai; Junzhi Zhou; Hu Wang (iScience)
Summary: Endothelial cell (EC) senescence is an accomplice for vascular aging, which leads to cardiovascular diseases (CVDs). Evidences showed that Hippo-Yes-associated protein (YAP) signaling pathway plays an essential role in aging-associated CVDs. Here, we reported that YAP was elevated in senescent human umbilical vein endothelial cells (HUVECs) and inhibition of YAP could attenuate HUVECs senescence. Besides, our findings revealed that the activity of UFMylation and the level of YAP were both elevated in senescent cells. Furthermore, UFM1-modified YAP was upregulated in senescent ECs, and increased the stability of YAP. Importantly, we found that compound 8.5, an inhibitor of E1 of UFMylation, can alleviate vascular aging in aged mice. Together, our finding provides molecular mechanism by which UFMylation maintains YAP stability and exerts an important role in promoting cell senescence, and identified that a previously unrecognized UFMylation is a potential therapeutic target for anti-aging.